Technopreneurship 4.0: Shaping Sustainable Innovation for the Digital Economy - Rasya Islami Dwi Julitha; Muhammad Syafi’i A. Basalamah; Imaduddin Murdifin; Muh. Haerdiansyah Syahnur (IECON: International Economics and Business Conference, 2025)
The purpose of this study is to explore the future of technopreneurship in the context of sustainable innovation and the evolving digital economy. It aims to analyze how technopreneurs can integrate sustainability principles into technological innovation to meet global demands for greener, smarter, and more inclusive economic development. Using a qualitative-descriptive approach, this study investigates key drivers, challenges, and strategies adopted by emerging digital entrepreneurs to balance profitability with social and environmental responsibility. The data were collected through in-depth interviews with 12 technopreneurs aged between 25 and 40 years, actively running digital-based start-ups in Indonesia, particularly in sectors such as e-commerce, agritech, edtech, and green energy. Additional insights were obtained from three innovation experts and two policymakers in the digital economy sector. Literature review and case study analysis were also conducted to support the triangulation of data. This research utilizes the Triple Bottom Line (TBL) framework—People, Planet, and Profit—as an analytical lens to evaluate how digital business models can evolve to address sustainability goals while remaining competitive. SWOT and PESTEL analyses were used to identify internal capabilities and external environmental factors influencing technopreneurship. Findings reveal that technopreneurs who adopt circular economy models, utilize renewable technologies, and embed ethical digital practices tend to gain stronger market positioning, consumer trust, and long-term viability. The study concludes that sustainable innovation is not only an ethical imperative but also a strategic advantage in the digital economy. These insights offer practical recommendations for entrepreneurs, educators, and policymakers in shaping a resilient and sustainable digital future.